Arvcf Dependent Adherens Junction Stability is Required to Prevent Age-Related Cortical Cataracts - Martin, Jessica B.; Herman, Kenneth; Houssin, Nathalie S.; Rich, Wade; Reilly, Matthew A.; Plageman, Timothy F. (Frontiers in Cell and Developmental Biology, 2022)
Abstract: The etiology of age-related cortical cataracts is not well understood but is speculated to be related to alterations in cell adhesion and/or the changing mechanical stresses occurring in the lens with time. The role of cell adhesion in maintaining lens transparency with age is difficult to assess because of the developmental and physiological roles that well-characterized adhesion proteins have in the lens. Here, ARVCF, a member of the p120-catenin subfamily of catenins that bind to the juxtamembrane domain of cadherins, is demonstrated to be an essential protein in preserving lens transparency with age in mice. No major developmental defects are observed in the absence of Arvcf, however, cortical cataracts emerge in all animals examined older than 6-months of age. While opacities are not obvious in young animals, histological anomalies are observed in lenses at 4-weeks that include fiber cell separations, regions of hexagonal lattice disorganization, and absence of immunolabeled membranes. Proteomic screening and immunofluorescent labeling of control and Arvcf-deficient lens fiber cells and lysates revealed a reduction in membrane localization and complex formation of N-cadherin, -catenin, and N-catenin. Furthermore, super-resolution imaging demonstrated that the reduction in protein membrane localization is correlated with smaller cadherin nanoclusters. Additional characterization of lens fiber cell morphology with electron microscopy and high resolution fluorescent imaging also showed that the cellular protrusions of fiber cells are abnormally elongated with a reduction and disorganization of cadherin complex protein localization. Finally, compression analysis of whole lenses revealed that that Arvcf is required for its normal biomechanical properties. Together, these data demonstrate that Arvcf is required to maintain transparency with age by mediating the stability of the N-cadherin protein complex in adherens junctions.